PENGEMBANGAN VIDEO ANIMASI 3D BERBASIS AI SEBAGAI MEDIA PEMBELAJARAN MATERI PECAHAN SENILAI PADA KELAS IV GUNA MENDUKUNG INOVASI GURU DAN MINAT BELAJAR SISWA - Anis Thasia; Raden Wisnu Wijaya Dewojati (CV. ADIBA ASIHA AMIRA, 2026)
The purpose of this study is to develop a 3D animated video media based on Artificial Intelligence (AI) on the topic of equivalent fractions for fourth-grade elementary school students. This research is motivated by students' low understanding of the abstract concept of fractions and the limited use of innovative learning media. The method used in this study is Research and Development (R&D) with the ADDIE model (analysis, design, development, implementation, and evaluation). The research subjects consisted of three experts, one teacher, and 11 fourth-grade students at SD Negeri 8 Simpang Pesak. Data collection techniques used observation, interviews, and questionnaires, while data analysis was carried out qualitatively and quantitatively. The results showed that the media obtained an expert validation score of 87.33% with a